Handbook of ethical educational leadership - Branson, Christopher M.; Gross, Steven Jay. (New York : Routledge, 2014)
'For the very first time, the Handbook of Ethical Educational Leadership brings together an array of key authors to provide comprehensive coverage of the field of ethical educational leadership. Describing contemporary educational issues that necessitate the practice of ethical leadership, this volume also explores a comprehensive and coherent framework for how ethical educational leadership can be achieved and reviews current theory and research-informed practices. Each chapter contributes to a comprehensive discussion and analysis of the field of ethical educational leadership. Providing practical, philosophical, and experiential insights, this volume is an important resource for the study of ethical leadership.'--
'The Routledge Handbook of Ethical Educational Leadership is the most up-to-date and comprehensive guide to the theory and practice of ethical educational leadership. This handbook of ethical educational leadership draws upon an array of literature from authors directly or indirectly associated with the Center for the Study of Leadership and Ethics (CSLE), which is a Program Center affiliated with the University Council for Educational Administration (UCEA). As a result of the internationalization of this particular Program Center in recent years, it is to become the UCEA Consortium for the Study of Leadership and Ethics in Education (CSLEE). Together this literature provides teachers, scholars and students with a coherent and broad-ranging insight into the current thinking and research associated with ethical educational leadership. Through detailed descriptions of contemporary theoretical precepts, qualitative and quantitative research, and extensive practical applications, readers of this handbook are provided with an extensive array of knowledge and understanding in this increasingly important field. Key topics covered in this handbook include: - Professionalism - Educational purpose - Social justice - Multiculturalism - Socio-political awareness - Sustainability - Empathy and caring - Organizational culture and ethics - Ethical leadership - Developing ethical leadership - Moral development - Ethical decision making - Moral motivation - Moral integrity - Values'--
Contents note continued: 16. Using Turbulence Theory to Guide Actions / Neil Cranston / Lisa C. Ehrich / Megan Kimber -- 17. Maintaining Moral Integrity / Steven Jay Gross -- 18. An Insight Into the Nature of Ethical Motivation / Christopher M. Branson -- 19. Deconstructing Ethical Motivation / Michael Bezzina / Nancy Tuana -- 20. Holistic and Moral Development of Educational Leaders / Christopher M. Branson -- 21.A Measure of Ethics / Anthony H. Normore / Tammy Schilling / Pauline E. Leonard -- 22. Ethical Responses to Educational Policies / Lyse Langlois / Claire Lapointe -- 23. The Ethical Perspectives of Turkish School Leaders / Joan Poliner Shapiro / Stephen Jay Gross -- 24. Preparation of Integrity / Mualla Aksu / Gamze Kasalak -- 25. Striving for Moral Purpose / John F. Covaleskie / William C. Frick -- 26. The Ethical Demands of Multiculturalism / Michael Bezzina / Charles Burford -- 27. Conclusion: If It Isn't Ethical, It Isn't Leadership / Katarina Norberg / Olof Johanson.
Includes bibliographical references and index.
Keywords: Educational leadership -- Moral and ethical aspects; Education -- Moral and ethical aspects